Problematika Ontologis Pendidikan Islam - Syaripudin Basyar (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Theefforts to understand ontological meaning of Islamic education are not easy, furthermore the nature of Islamic education meaning is intended as an abstraction integrity of meaning that is accepted ideological, theoretical, and empirical. The existence of Islamic education is always in contact and grappling with the reality surrounding them. In historical perspective, the struggle between Islamic educations with socio-cultural realities faces two possibilities: influences or is influenced. The consequence is that Islamic education can be defined as a process of enculturation and or facilitation efforts (medium). If referring to the terms of Islam, Islamic education is personified to the term attarbiyah, at-ta'lim, at-ta'dib and ar-riyadah. Each of these terms has different accentuation meanings although it has the same outline. In understanding Islamic education, basic education and its goal formulation becomes noteworthy. Since the basis and purpose of demarcation will distinguish with other educations.